2021
DOI: 10.1111/avsc.12580
|View full text |Cite
|
Sign up to set email alerts
|

Mapping structural attributes of tropical dry forests by combining Synthetic Aperture Radar and high‐resolution satellite imagery data

Abstract: Aim Optical satellite imagery has been used for mapping the spatial distribution of vegetation structure attributes; however, obtaining accurate estimates with optical imagery can be difficult in tropical forests due to their dense canopy and multi‐layered vegetation. Synthetic aperture radar imagery can be more suitable in this case, as the radar signal can penetrate the forest canopy and interact with stems, providing a better estimation of the vegetation structure. This study compared the accuracy of forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…However, the coefficients of determination and the estimation error in the validation with a separate dataset show the predictive power of the models (R 2 = 0.44 and %RMSE = 25.4 for species richness; R 2 = 0.50 and %RMSE = 48.8, for functional diversity). Estimates of the spatial distribution of species richness showed patterns similar to those reported by Hernández-Stefanoni et al [22] and Andres-Mauricio et al [55], who constructed maps of tree species richness in the Yucatan Peninsula. However, this study showed a higher predictive power than the previous investigations, which yielded lower coefficients of determination and higher estimation errors.…”
Section: Evaluation Of Species Richness and Functional Richness Mapssupporting
confidence: 82%
“…However, the coefficients of determination and the estimation error in the validation with a separate dataset show the predictive power of the models (R 2 = 0.44 and %RMSE = 25.4 for species richness; R 2 = 0.50 and %RMSE = 48.8, for functional diversity). Estimates of the spatial distribution of species richness showed patterns similar to those reported by Hernández-Stefanoni et al [22] and Andres-Mauricio et al [55], who constructed maps of tree species richness in the Yucatan Peninsula. However, this study showed a higher predictive power than the previous investigations, which yielded lower coefficients of determination and higher estimation errors.…”
Section: Evaluation Of Species Richness and Functional Richness Mapssupporting
confidence: 82%
“…Conversely, texture metrics had a higher influence on species richness (7.3%) compared to backscatter (0.02%). SAR sensorssuch as ALOS PALSAR-with large wavelengths can easily penetrate the forest canopy, allowing accurate estimates of basal area, diameter and tree height, all which are related to biomass [63]. Meanwhile, texture metrics that measure spectral variability have been closely related to species richness [64], as these metrics are proxies of habitat heterogeneity.…”
Section: Evaluation Of Carbon Density and Species Richness Mapsmentioning
confidence: 99%
“…The early studies attempting to estimate biomass using satellite remote sensing variables utilized Landsat TM data with 30 m resolution [13][14][15] in structurally simple temperate and boreal forests. Vegetation indexes were the most frequently employed approach in optical remote sensing for biomass estimation [16]. Most indices rely on the connection between red and near-infrared wavelengths to maximize the spectral input from green vegetation while minimizing contributions from the soil, sun angle, sensor view angle, shaded vegetation, and atmosphere [17].…”
Section: Introductionmentioning
confidence: 99%